The Impact of Caregiving on the Association Between Infant Emotional Behavior and Resting State Neural Network Functional Topology - Hanford, Lindsay C.; Schmithorst, Vincent J.; Panigrahy, Ashok; Lee, Vincent; Ridley, Julia; Bonar, Lisa; Versace, Amelia; Hipwell, Alison E.; Phillips, Mary L. (Frontiers in Psychology, 2018)
The extent to which neural networks underlying emotional behavior in infancy serve as precursors of later behavioral and emotional problems in unclear. Even less is known about caregiving influences on these early brain-behavior relationships. To study brain-emotional behavior relationships in infants, we examined resting-state functional network metrics and infant emotional behavior in the context of early maternal caregiving. We assessed 46 three-month-old infants and their mothers from a community sample. Infants underwent functional MRI during sleep. Resting-state data were processed using graph theory techniques to examine specific nodal metrics as indicators of network functionality. Infant positive and negative emotional behaviors, and positive, negative and mental state talk (MST) indices of maternal caregiving were coded independently from filmed interactions. Regression analyses tested associations among nodal metrics and infant emotionality, and the moderating effects of maternal behavior on these relationships. All results were FDR corrected at alpha=0.05. While relationships between infant emotional behavior or maternal caregiving, and nodal metrics were weak, higher levels of maternal MST strengthened associations between infant positive emotionality and nodal metrics within prefrontal (p<0.0001), and occipital (p<0.0001) cortices more generally. Positive and negative aspects of maternal caregiving had little effect. Our findings suggest that maternal MST may play an important role in strengthening links between emotion regulation neural circuitry and early infant positive behavior. They also provide objective neural markers that could inform and monitor caregiving-based interventions designed to improve the health and well-being of vulnerable infants at-risk for behavioral and emotional problems.